Konsep Akhlak Menurut Pemikiran Imam Al-Ghazali dan Buya Hamka (Suatu Perbandingan dengan melalui Pendekatan Filosofis) - Dayantri, Misra Nova; Sapri, Sapri (Lembaga Yasin AlSys, 2024)
The phenomenon of moral decline has been going on for a long time. There are various strategies and efforts made by various groups to modify current conditions. Many efforts have been made to improve the quality of education by changing the curriculum. However, of the many curriculum changes that have been made, until now the benefits have not been felt significantly. Islam has a deep understanding of education. Before starting the learning process, a student or student needs to have or learn good manners first. This has been done by Islamic scientists for a long time. The aim is none other than so that the people produced from an educational institution are people with good morals. Therefore, in this research, the researcher will discuss the concept of morals according to the thoughts of a Muslim scholar who is famous for his moral theory. Therefore, the researcher hopes that this research will be able to help in finding solutions to the current moral situation. This research uses a library research methodology with a qualitative research type, namely using a data and reading approach based on library research. Imam Al-Ghazali and Buya Hamka have similarities in their thoughts about the nature of morals, namely that they both prioritize good morals with an emphasis on human efforts to achieve moral perfection consisting of four types, namely hikmah, syajaah, 'iffah and 'adl. The difference in the moral thinking of these two figures can be seen from the background of their thinking. Imam Al-Ghazali's thoughts about morals are the result of the emergence of human life, at that time worldly life came first while life in the afterlife came second. Meanwhile, Buya Hamka's thoughts live in modern times, which coincides with the period of colonialism and Indonesian independence.